Clinical Outcome with Oral Linezolid and Rifampin Following Recurrent Methicillin-Resistant Staphylococcus aureus Bacteremia Despite Prolonged Vancomycin Treatment - Jon-David Schwalm; Philippe El-Helou; Christine H Lee (Canadian Journal of Infectious Diseases)
Drug-resistant Gram-positive bacteria, especially Staphylococcus aureus, are emerging as the predominant organisms involved in both nosocomial and community-acquired infections. Since the 1980s, vancomycin has been the first-line antibiotic used to treat methicillin-resistant S aureus. However, allergy and intolerance to vancomycin, the increasing number of vancomycin clinical failures and the existence of vancomycin intermediate-susceptible isolates of S aureus suggest that new antibiotics are needed. This paper reports the only known case of a successful clinical outcome with long term oral linezolid and rifampin therapy in the management of recurrent and persistent methicillin-resistant S aureus bacteremia with metastatic infections despite prolonged vancomycin use. More than two years since the initiation of linezolid and rifampin, the study patient has been clinically well with no evidence of adverse drug reactions including cytopenia and hepatic toxicities. Physicians must be aware of the novel developments in antibiotic therapy to treat drug-resistant bacterial infections.